PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN KOMIK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 4 BAYAN PADA MATERI GARIS DAN SUDUT TAHUN AJARAN 2023/2024 - Leni Herawati; Ketut Sarjana; Syahrul Azmi; Nani Kurniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of using comic-based learning media on students' learning outcomes in mathematics for seventh-grade students at SMP Negeri 4 Bayan. Initial observations indicated that the low mid-semester exam results were due to students' difficulties in understanding the material and the perception that mathematics is uninteresting. The research method used was experimental, with class VII A as the experimental group and class VII B as the control group. The research instruments included tests and student activity observation sheets. Data analysis results showed that student activity in the experimental class reached the very active category, while the control class reached the active category. The average score of the experimental class was 89.04, higher than the control class's 68.15. Statistical analysis data showed a sig. value of 0.001 < 0.05 with t_(calculated) = 8.267 ≥ t_(table) = 2.00, indicating a significant difference between the learning outcomes of the experimental and control classes. This difference was due to the experimental class using comic-based media while the control class did not. It can be concluded that the use of comic-based media has a significant effect on improving learning outcomes in the topic of lines and angles.